Physical exercise and mathematical anxiety: a neuroscience-based perspectivefor math education. - Mauro Roberto de Souza Domingues; Marcos Guilherme Moura Silva; Felipe Barradas Cordeiro; Mizael Carvalho de Souza; Renan Wallace Guimarães da Rocha; Natáli Valim Oliver Bento Torres; João Bento Torres Neto (Amazônia, 2022)
In this paper we analyze the effects of physical exercise on the brain, on cognitive/school performance and on mental health from a Neuroscience perspective, in association with Mathematical Anxiety (MA). Physical exercise promotes structural and functional benefits to the nervous system, improves cognitive performance and anxiety. The evidence provide support to the effects of physical exercise on decreased matemathical anxiety in school-age children. We address discussion to improve viable educational strategies for the improvement of students physical, cognitive and mathematical performance.